Patterns of isozyme variation in the Leucaena shannonii alliance (Leguminosae: Mimosoideae) - Chamberlain, JR; Hughes, C; Galwey, N (1996)
Genetic variation within, and the relationships between, 4 taxa that comprise the Leucaena shannonii alliance were analysed with isozymes. Six enzyme systems were used to analyse 2 natural populations of L. salvadorensis STANDLEY ex. B. and R., 2 of L. shannonii DONN. SMITH subsp. magnifica C.E. HUGHES, 4 of L. shannonii DONN. SMITH subsp. shannonii and 2 populations of an undescribed taxon, L. sp. nov., Cluster analysis of NEI'S genetic distances (NEI, 1978) and Population Aggregation Analysis (PAA) (DAVIS and NIXON, 1992) were used to delimit species. L. sp. nov. was found to be most closely related to L. salvadorensis, however, isozyme variation did not support a close relationship between the 2 subspecies of L. shannonii. The level and structure of genetic variation within species of the alliance was also assessed. L. shannonii subsp. shannonii was found to be the most diverse taxon, and subsp, magnifica the least diverse. It is postulated that this may contribute to the apparent dissimilarity of the 2 taxa in the cluster analysis. The use of PAA to delimit species in the L. shannonii alliance is also discussed.